Building educators' confidence and skill in improvement science: a longitudinal study of the STEM PUSH Network - Lin, Yiwen; Iriti, Jennifer; Sherer, Jennifer Zoltners; Lowry, Danielle; Matthis, Christopher; Legg, Alison Slinskey (Frontiers in Education, 2025)
Networked Improvement Communities (NICs) are a promising strategy for professional learning and educational change. However, limited empirical research has quantitatively examined how network participation cultivates educators' improvement science capacities. This study draws on four years of longitudinal data from the STEM PUSH Network—a NIC designed to broaden participation in STEM through collaboration with leaders of pre-college STEM programs. We investigate how deliberate practice and social learning, two central components of the NIC model, shape the development of improvement science confidence and skill. Our findings show that social learning is most strongly associated with educators' confidence in using improvement tools, while meaningful participation in structured improvement groups predicts demonstrated skill. We also find that network tenure—longer-term engagement and sustained exposure to improvement work—is critical for both outcomes. Together, these findings offer the first quantitative and longitudinal evidence of the distinct and nuanced ways NIC participation shapes practitioners' confidence and skill in improvement science. We conclude by discussing implications for future research and practice in the design and facilitation of Networked Improvement Communities.